Growth of 'Seascape' strawberry (Fragaria X ananassa Duch.) is altered by photoperiod and nitrogen conditioning. Issue 5 (2nd September 2020) - Durner, Edward F.
ABSTRACT: The influences of photoperiod and nitrogen plug conditioning for summer planting of 'Seascape' strawberry ( Fragaria x ananassa Duch.) for off-season plasticulture production were evaluated in two separate experiments in New Jersey, USA. In experiment one, plants were conditioned in the greenhouse under ND (natural daylength), LD (ND supplemented with 24 h incandescent radiation (Phillips Duramax Soft White A19 60 watt) or LD7W (ND supplemented with 24 h incandescent radiation (C9, 7 watt bulbs) followed by elevated nitrogen (800 ppm) for 0 to 4 weeks. In experiment two, plants were conditioned in the greenhouse under ND or LD followed by elevated nitrogen (800 ppm) for 4 weeks. In experiment one, flowering was enhanced by LD conditioning. The 24LD7W treatment was more effective than the 24LD treatment in eliciting a long day response at low levels of N (0 and 1 week of elevated N) but not at higher levels of N (2 to 4 weeks of elevated N). No treatment effects were observed for fruit production. In the second experiment, flowering was enhanced by LD or elevated N. Elevated nitrogen during conditioning slightly enhanced yield through 11 September while photoperiod during conditioning did not affect productivity. Runner production was minimal in both experiments.